Pengembangan Website Penjualan W’D Cakes & Cookies dengan Integrasi CRM dalam Meningkatkan Loyalitas Pelanggan - Renaldi Yulvianda; Muhammad Ismail; Mochammad Arief Hermawan Sutoyo (Jurnal Ilmiah Sistem Informasi (JISI), 2025)
The food and beverage industry, particularly the bakery and pastry sector, is growing rapidly due to increasing consumer demand and changes in consumption behavior. MSMEs like W’D Cakes & Cookies face operational challenges because they still rely on manual ordering systems via WhatsApp, which are prone to recording errors, service delays, and inefficient customer data management. This study aims to develop a web-based sales system integrated with Customer Relationship Management (CRM) to improve operational efficiency and customer loyalty. The research applies the Research and Development (R&D) method using the waterfall model, which includes requirement analysis, system design using Figma, development using the Laravel framework, and testing through Black Box Testing. The system implementation supports online ordering, product and customer management, digital payments, and transaction tracking. The embedded CRM features enable loyalty analysis, personalized promotions, and targeted customer communications. This system contributes to the digital transformation of MSMEs, increasing transaction speed, data accuracy, and service quality. Future research may explore integration with e-commerce platforms, chatbot implementation for customer service automation, and the use of artificial intelligence (AI) analytics to support data-driven marketing strategies.